Risk Management, Sharia Compliance, and the Performance of Islamic Insurance Companies in Indonesia - Adelia Putri Harahap; Wahyu Syarvina; Nur Ahmadi Bi Rahmani (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
This study examines the effect of Risk-Based Capital (RBC) on the profitability of Sharia insurance companies in Indonesia and provides descriptive evidence on institutional Sharia compliance through the existence of the Sharia Supervisory Board (Dewan Pengawas Syariah/DPS). The study uses secondary data from the financial statements and public reports of Sharia insurance companies for the 2020-2024 period, producing 30 firm-year observations. Profitability is proxied by Return on Assets (ROA), risk management is proxied by RBC, and Sharia compliance is observed descriptively through DPS existence. Because all observations have a DPS value of 1, the Sharia compliance variable has no statistical variation and therefore cannot be included in the regression model. The analysis uses descriptive statistics, classical assumption tests, and a log-linear regression model. The descriptive results show that RBC ranges from 120.00 to 671.23, with an average value of 236.35, while ROA averages 0.020763 or approximately 2.07%. The regression results show that LN_RBC has a negative but statistically insignificant coefficient on LN_ROA (coefficient = -0.739; t = -1.484; p = 0.149). The coefficient of determination is 0.073, indicating that RBC explains only 7.3% of the variation in ROA. These findings suggest that solvency-oriented capital adequacy does not automatically translate into higher short-term profitability. The profitability of Sharia insurance companies is more likely to be shaped by underwriting quality, claim ratio, expense ratio, investment return, firm size, leverage, and operational efficiency. The study contributes by clarifying the empirical limitation of using a binary DPS variable as a Sharia compliance proxy and recommends that future studies construct a more comprehensive Sharia compliance index.